(untitled) - Bosch, Sammy (Minneapolis, Minnesota, 2016)
These projects will get kids crafting while they learn about different zoo animals.
Zoo critters -- Get to know zoo animals! -- All about zoos -- Materials -- Trumpeting elephant -- Roly-poly penguins -- Tiny tiger puppet -- Tall tube giraffe -- Rock 'em sock 'em gorilla -- Plush polar bear -- Howling wolf puppet -- Fluffy peacock pal.
Keywords: Juvenile literature; Zoo animals; Handicraft; Handicraft; Zoo animals; Juvenile literature; Decorative arts